Project monitoring systems (PMS II) - case study on the constraints and problems facing at users level - Abdul Hamid, Mohd. Faisal (2006)
An effective and efficient monitoring system to the projects development is the most important aspect in order to ensure their implementation will going smoothly and not be affected due to the current phenomenon of world economic. As a general the process of monitoring is included planning, implementation and evaluation of the projects to make sure all development projects can be done consistently at all level and any problem occurs will straight away taken into action. An efficiency of monitoring system always needs to be upgraded from time to time with the introducing of some new method or system from the government due to the current technology changing. There are many system has been introduced corresponding to the Five Year Malaysian Plan and Long Term Planning (Outline Perspective Plan). Since from the day of independent projects monitoring system already exist such as Red Book, Project Monitoring System I, SETIA System, Integration and Planning Application System, SMBSS, and the latest one is Project Monitoring System II (PMS II). All these systems has been developed and implemented to ensure all the development projects that have been planned by the government can be succeed to fulfill the government policies such as New Economy Policy, National Development Policy and National Vision Policy. This study will narrow down to the PMS II and it application to the government agencies. The main focus is to study and explore the using of PMS II and the problems facing when to key-in the current data for the projects.